Thermal limits of activity and survival in false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae) : life-stage and ramping rate effects - Uys, Wilmari (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.